2022
DOI: 10.3390/agronomy12112884
|View full text |Cite
|
Sign up to set email alerts
|

Application of Spent Sun Mushroom Substrate in Substitution of Synthetic Fertilizers at Maize Topdressing

Abstract: Synthetic fertilization can increase maize yields, but also cause environmental impacts, as well as increasing production costs and food security risks. Sun mushroom (Agaricus subrufescens) is an important Brazilian fungus used to generate large amounts of spent mushroom substrate. This residue can be used for maize fertilization, but little is known about its ideal application rates to reduce maize dependence on synthetic fertilizers. Therefore, this study aimed to evaluate the agronomic performance of a maiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…As an advantage, maize cultivation in post-harvest areas can be a cost-effective and sustainable alternative to synthetic fertilization, due to the presence of organic residues from mushroom cultivation already present in the soil. Moreover, soil pH (6.1 to 6.6) and EC levels (75-159 µS cm -1 ) were found to be within an acceptable range for all treatments and crops, as recommended in the literature (Medina et al 2012;Alves et al 2022). The SMS treatment was better in the rst season because it provided high levels of P, Ca and Mg in the soil (Table 3 and Fig.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…As an advantage, maize cultivation in post-harvest areas can be a cost-effective and sustainable alternative to synthetic fertilization, due to the presence of organic residues from mushroom cultivation already present in the soil. Moreover, soil pH (6.1 to 6.6) and EC levels (75-159 µS cm -1 ) were found to be within an acceptable range for all treatments and crops, as recommended in the literature (Medina et al 2012;Alves et al 2022). The SMS treatment was better in the rst season because it provided high levels of P, Ca and Mg in the soil (Table 3 and Fig.…”
Section: Discussionsupporting
confidence: 66%
“…Additionally, our study's ndings are supported by Mohapatra et al's (2020) research, which showed that areas previously cultivated for outdoor mushroom production can be reused to achieve increased yield. Speci cally, in previous studies, we proved that the addition of spent sun mushroom substrate increases the agronomic parameters of maize (Alves et al 2022).…”
Section: Discussionmentioning
confidence: 52%
“…Meanwhile, waste mushroom residue is rich in macro- and micronutrients, making it a viable option for organic fertilizer [ 18 , 19 ]. Previous studies have found that the appropriate combination of mineral fertilizers and waste mushroom residues is beneficial to improving and maintaining soil quality and plant growth [ 20 , 21 , 22 ]. As an important producer of mushrooms in China, Sichuan mainly produces Enoki mushroom, Oyster mushroom, Auricularia polytricha mushroom, Shiitake mushroom, and Agaricus bisporus [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several efforts have been made to develop efficient and sustainable strategies for the SMS valorization, including its application as an alternative fertilizer and soil amendment agent [9,10], as a supplement to enrich nutrient levels in subsequent mushroom cultivation cycles [11], as a soil bioremediation agent [12][13][14], and as a feedstock for biofuel production [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%